Pengetahuan Ibu Tentang Nutrisi Berhubungan dengan Kejadian Stunting di Puskesmas Minggir Sleman Yogyakarta - Qosim, Muhammad Nanang; Hutasoit, Masta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: The high prevalence of stunting in toddlers remains a priority problem in children under five years. The stunting rate in the Sleman Health Center work area is 13.16%; this is still far from the government's target of reducing stunting to 10% by 2024. Lack of nutritional intake in toddlers is the main predictor of the onset of malnutrition and malnutrition problems and impacts the incidence of stunting or wasting. Factors in stunted toddlers' lack of nutritional intake are maternal knowledge and maternal behavior in providing additional food. Nutritional knowledge that needs to be understood by a mother is an understanding of balanced nutrition so that the growth and development of toddlers can be optimal. Objective: This study aims to underscore the importance of maternal knowledge about nutrition in addressing the incidence of stunting in the work area of the Minggir Sleman Health Center, Yogyakarta. Methods: This study used a quantitative design with an observational analytic research design and a cross-sectional approach. The population in this study was 278, with a research sample of 54 respondents taken by purposive sampling. Data on maternal knowledge about nutrition was collected using a maternal knowledge questionnaire, and the incidence of stunting was assessed using secondary data from the MCH clinic—bivariate analysis using the Spearman Rank statistical test. Results: Regarding maternal knowledge about nutrition, most were in the sufficient category at 51.9%, and the nutritional status of toddlers was mostly in the normal category at 57.4%. There is a relationship between maternal knowledge about nutrition and the incidence of stunting with a p-value of 0.001 (<0.05) and relationship data of 0.420. Conclusion: This study's findings are significant, as they establish a clear relationship between maternal knowledge and the incidence of stunting in the work area of the Minggir Sleman Health Center. The strength of this relationship falls within the moderate category, underscoring the importance of maternal knowledge in addressing stunting in toddlers.